New Trends in Emerging Complex Real Life Problems ODS, Taormina, Italy, September 10-13, 2018 (AIRO Springer Series,, 2018)
This book gathers the contributions of the international conference "Optimization and Decision Science" (ODS2018), which was held at the Hotel Villa Diodoro, Taormina (Messina), Italy on September 10 to 13, 2018, and was organized by AIRO, the Italian Operations Research Society, in cooperation with the DMI (Department of Mathematics and Computer Science) of the University of Catania (Italy). The book offers state-of-the-art content on optimization, decisions science and problem solving methods, as well as their application in industrial and territorial systems. It highlights a range of real-world problems that are both challenging and worthwhile, using models and methods based on continuous and discrete optimization, network optimization, simulation and system dynamics, heuristics, metaheuristics, artificial intelligence, analytics, and multiple-criteria decision making. Given its scope of coverage, it will benefit not only researchers and practitioners working in these areas, but also the operations research community as a whole.